2018
DOI: 10.1016/j.jid.2017.09.052
|View full text |Cite
|
Sign up to set email alerts
|

RNase 7 Strongly Promotes TLR9-Mediated DNA Sensing by Human Plasmacytoid Dendritic Cells

Abstract: Plasmacytoid dendritic cells (pDCs) were described to accumulate in the skin of patients with psoriasis and to be recruited into the dermis upon allergen challenge in atopic dermatitis. Activation of pDCs in the skin has been identified as an important initiator of psoriasis development. Ribonuclease (RNase) 7 is one of the major antimicrobial peptides secreted by keratinocytes and is expressed in significantly higher amounts in lesional skin of patients with atopic dermatitis or psoriasis than in healthy indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 58 publications
0
44
0
Order By: Relevance
“…During normal cornification, keratinocytes express deoxyribonucleases (DNases) [ 12 ]; however, it was recently shown that reduced keratinocyte DNase activity in psoriasis results in suppressed DNA degradation and, as a consequence, parakeratosis [ 13 ] and the presence of excess DNA fragments in the cytosol. Similarly, disturbed ribonuclease activities were described in psoriatic skin [ 14 , 15 ], which might result in excess RNA fragments.…”
Section: Introductionmentioning
confidence: 89%
“…During normal cornification, keratinocytes express deoxyribonucleases (DNases) [ 12 ]; however, it was recently shown that reduced keratinocyte DNase activity in psoriasis results in suppressed DNA degradation and, as a consequence, parakeratosis [ 13 ] and the presence of excess DNA fragments in the cytosol. Similarly, disturbed ribonuclease activities were described in psoriatic skin [ 14 , 15 ], which might result in excess RNA fragments.…”
Section: Introductionmentioning
confidence: 89%
“…Finally, expression of the protein was recently reported to be induced in basal cells of damaged airway epithelia, reinforcing the idea of a protective role for this protein following tissue injury (Table 1 ) ( 70 ). A very recent study showed that this protein directly stimulated plasmocytoid DCs following tissue damage and infection, and the authors of the report proposed to classify hRNase7 as an alarmin ( 54 ). Interestingly, the immuno-modulatory activity of the RNase correlates with binding to self-DNA and activation of TLR9 receptors.…”
Section: The Rnase a Superfamilymentioning
confidence: 99%
“…In line with this, a novel mechanism of nucleic acid recognition by LL-37 utilizing cell surface RNA scavenger receptors (SRs) has been described [122], which results is enhanced clathrin-dependent endocytosis, facilitating the overproduction of inflammatory cytokines and chemokines. Recently also RNase7 was found to utilize plasmacytoid dendritic cell (pDC) TLR-9 signaling mode of IFN-α activation even more strongly than LL-37, emphasizing its crucial role in autoimmune inflammatory skin diseases [123]. Interestingly, other antimicrobial peptides expressed in the skin, such as psoriasin, elafin, or hBD-1, lack the ability of interacting with the host nucleic acids, which may be related to their lower net charge ( Figure 2) [120].…”
Section: Molecular Mechanisms Of Anti-and Pro-inflammatory Action Of mentioning
confidence: 99%